Association between Biochemical Vitamin A Deficiency, Xerophthalmia, and Dermatological Manifestations among School-Aged Children. - Shahid, Resham; Jamil, Farrakh; Abid, Abdul Rahman; Afridi, Saleha; Perveen, Zahida; Manzoor, Amna (Journal of Neonatal Surgery, 2025)
Background: Vitamin A deficiency (VAD) remains a major public health concern among children in developing countries. Although xerophthalmia is the classical ocular manifestation, dermatological signs such as follicular hyperkeratosis, phrynoderma, and xerosis may occur earlier and could serve as clinical indicators of subclinical deficiency. Objective: To determine the association between biochemical Vitamin A deficiency, xerophthalmia, and dermatological manifestations among children aged 5–15 years. Methods: A cross-sectional study was conducted among 300 school-aged children in Lahore and Rawalpindi/Islamabad from January 2025 to July, 2025. Ocular examination was performed to identify signs of xerophthalmia, and dermatological assessment focused on follicular hyperkeratosis, phrynoderma, and generalized xerosis. Serum retinol levels were measured using high-performance liquid chromatography (HPLC). Vitamin A deficiency was defined as serum retinol <0.70 µmol/L. Data were analyzed using chi-square test and logistic regression, with p <0.05 considered statistically significant. Results: Vitamin A deficiency was identified in 24% of participants. Xerophthalmia was observed in 13%, whereas dermatological manifestations were present in 27% of children. Among Vitamin A–deficient children, 58.3% exhibited dermatological signs compared with 17.5% in non-deficient children (p <0.001). Xerophthalmia showed a significant association with low serum retinol levels (p <0.001). Vitamin A-deficient children had 4.2 times higher odds of developing dermatological manifestations (OR = 4.2; 95% CI: 2.3–7.6). A moderate positive correlation was observed between severity of cutaneous findings and degree of retinol deficiency (r = 0.46, p <0.001). Conclusion: Vitamin A deficiency is significantly associated with xerophthalmia and dermatological manifestations among school-aged children. Cutaneous signs may serve as early clinical markers of biochemical deficiency. Integrating dermatological screening with ocular assessment in school health programs may facilitate early detection and prevention of sight-threatening complications...